Hubungan Pengetahuan Ibu Tentang Gizi Seimbang dengan Status Gizi Balita di Desa Mulyorejo, Kec. Kraton, Kab. Pasuruan - Lailatul Nujulah (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
One determinant of the quality of Human Resources is nutrition, poor nutritional status can result in developmental failure and physical growth, work productivity and decreased immunity, which can result in pain and even death. Based on Nutritional Status Monitoring in Mulyorejo village in June 2017, there were 16 infants (10.12%) from a total of 158 toddlers. One of the malnutrition is caused by a lack of level of knowledge about balanced nutrition in toddlers' mothers. To find out whether there is a relationship between maternal knowledge about balanced nutrition and nutritional status of children in Mulyorejo Village, Kraton Sub-District, Pasuruan Regency. The method used in this study was an observational analytic cross sectional study, with 38 mothers of infants and toddlers aged 1-5 years. Purposive sampling is a technique used for sampling in this study. Based on the results of the Spearman test, the p value is 0.034 with the correlation coefficient of 0.345, which means that there is a relationship between maternal knowledge of balanced nutrition and the nutritional status of children in Mulyorejo Village, Kraton District, Pasuruan Regency which shows a low level of relationship. There is a relationship between mother's knowledge of balanced nutrition and nutritional status of children in the village of Mulyorejo, Kec. Kraton, Kab. Pasuruan.\Keywords: Knowledge, balanced nutrition, toddler nutritional status.